Spatial distribution and analysis of soil loss over micro watersheds of Sierra de Vaqueros (Salta, Argentina) by using a GIS - Moreno, Ramona Ignacia; Campos, Pablo Alejandro; Avendaño, Adrián José; Núñez, Virgilio; Gil, Mirian Norma; Salas Barboza, Ariela Griselda Judith; Medina, Eliseo Pedro Joel (Pontificia Universidad Católica del Perú. Fondo Editorial, 2017)
Immediately north of Salta city, several streams have their sources on the eastern slopes of the Sierra de Vaqueros, whose piedemonte is urbanized. The man influence on the mountain environment makes it necessary to estimate erosion rates the location of their different erosion classes and their analysis. The work was carried out with satellite images, generating the base map and thematic maps of the Vaqueros and Los Nogales microbasins, through the use of a Geographic Information System (GIS); this allowed to characterize the study areas and to obtain the necessary information to apply the Universal Equation of Soil Loss (USLE). R, K and LS factors were obtained through adaptations of the method, due to the unavailability of data established by authors. The average of current water erosion showed a rate of 47 t/ha/year for the Vaqueros microbasin and 45 t/ha/year for the microbasin Los Nogales. The different categories of erosion were located and analyzed considering the interaction of the acting factors. For the achievement of a better environmental quality simple measures to influence the possible factors to be modified were proposed.

Inmediatamente al norte de la ciudad de Salta, varios arroyos tienen sus nacientes en las laderas orientales de la Sierra de Vaqueros, cuyo piedemonte se encuentra urbanizado. La influencia del hombre sobre el ambiente serrano determina la necesidad de estimar las tasas de erosión, localizar las diferentes clases de pérdida de suelos y llevar a cabo su análisis. Se trabajó con imágenes satelitales, generándose los mapas base y temáticos necesarios de las microcuencas de los arroyos Vaqueros y Los Nogales, mediante la utilización de un Sistema de Información Geográfica (SIG). Esto permitió caracterizar las áreas de estudio y lograr la información nece- saria para aplicar la Ecuación Universal de Pérdida de Suelos (USLE). Los factores R, K y LS se obtuvieron mediante adaptaciones del método, en razón de la indisponibilidad de datos establecidos por los autores. El promedio de la pérdida de suelos actual corresponde a una tasa de 47 t/ha/año para la microcuenca Vaqueros y de 45 t/ha/año para la del arroyo Los Nogales. Las diferentes categorías de erosión fueron localizadas y analizadas considerando la interacción de los factores actuantes. Para el logro de una mejor calidad ambiental, se propusieron medidas sencillas con el fin de incidir sobre los factores que pueden ser modificados.
Keywords: Geografía; https://purl.org/pe-repo/ocde/ford#5.07.00